2014
DOI: 10.5194/acp-14-10383-2014
|View full text |Cite
|
Sign up to set email alerts
|

Constraining CO<sub>2</sub> emissions from open biomass burning by satellite observations of co-emitted species: a method and its application to wildfires in Siberia

Abstract: Abstract. A method to constrain carbon dioxide (CO2) emissions from open biomass burning by using satellite observations of co-emitted species and a chemistry-transport model (CTM) is proposed and applied to the case of wildfires in Siberia. CO2 emissions are assessed by means of an emission model assuming a direct relationship between the biomass burning rate (BBR) and the fire radiative power (FRP) derived from MODIS measurements. The key features of the method are (1) estimating the FRP-to-BBR conversion fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(142 citation statements)
references
References 98 publications
(152 reference statements)
12
130
0
Order By: Relevance
“…The thermal radiation recorded in satellite products is additionally reduced by cloud cover and erroneous flagging of smoke as clouds during data processing. Konovalov et al (2014) nevertheless found FRE-to-DM relationships relatively similar to those of the earlier small-scale experiments when using atmospheric observations and biomass burning trace gas and aerosol emissions factors to estimate fuel consumption. Exploring methods to incorporate the fire diurnal cycle in the GFAS global FRP-based near real time emission inventory is a first step in taking into account some of these issues in order to improve global FRE estimates made at relatively high spatiotemporal resolutions, and hopefully also in reconciling some of the differences in current emission inventories.…”
Section: Model Performance and The Modis Sampling Designmentioning
confidence: 48%
See 1 more Smart Citation
“…The thermal radiation recorded in satellite products is additionally reduced by cloud cover and erroneous flagging of smoke as clouds during data processing. Konovalov et al (2014) nevertheless found FRE-to-DM relationships relatively similar to those of the earlier small-scale experiments when using atmospheric observations and biomass burning trace gas and aerosol emissions factors to estimate fuel consumption. Exploring methods to incorporate the fire diurnal cycle in the GFAS global FRP-based near real time emission inventory is a first step in taking into account some of these issues in order to improve global FRE estimates made at relatively high spatiotemporal resolutions, and hopefully also in reconciling some of the differences in current emission inventories.…”
Section: Model Performance and The Modis Sampling Designmentioning
confidence: 48%
“…For the same reason, temperate and boreal forests have been reported to show a more pronounced diurnal cycle than grasslands ( Fig. 2; Sofiev et al, 2013;Konovalov et al, 2014). Building on the land cover based analysis of Roberts et al (2009), we provide a first analysis of the spatial distribution of the fire diurnal cycle.…”
Section: N Andela Et Al: New Fire Diurnal Cycle Characterizations Tmentioning
confidence: 99%
“…Emissions from forest fires (van der Werf et al, 2006;Sofiev et al, 2013) and from agricultural fires in southern Siberia, Kazakhstan, and Ukraine (Korontzi et al, 2006) in spring and summer are large sources of trace gases such as carbon monoxide (Nédélec et al, 2005;Konovalov et al, 2014) as well as aerosol particles (Konovalov et al, 2015). Aerosols emitted by forest fires are of particular interest, since the strength of this source type depends on both climate change and human behaviour (Pechony and Shindell, 2010), and since particles emitted by these fires have potentially large radiative effects over Eurasia (Randerson et al, 2006).…”
Section: Large-scale Pollutant Transport and Sourcesmentioning
confidence: 99%
“…During and after fires, significant changes take place in the forest ecosystems, including the soil. These changes include (i) a significant amount of biomass is combusted, and large amounts of carbon and nitrogen are released to the atmosphere in the form of carbon dioxide and other gases or particles (Harden et al, 2000;Andreae and Merlet, 2001;Kaiser et al, 2012;Konovalov et al, 2014;; (ii) fire alters the microbial community structure in the soil as well as the structure of the vegetation (Dooley and Treseder, 2012;Sun et al, 2015); (iii) fires determine the structure of the vegetation, succession dynamics and the fragmentation of forest cover, tree species composition, and the productivity of boreal forests (Gewehr et al, 2014), and (iv) fire is one of the crucial drivers controlling the dynamics of the carbon stock of boreal forests (Jonsson and Wardle, 2010;Köster et al, 2014).…”
Section: Natural Hazards Extreme Weather and Fire Occurrencementioning
confidence: 99%
“…In the second approach, Berezin et al (2013) estimated multiannual relative changes of FF CO 2 emissions from China by using satellite measurements of nitrogen dioxide (NO 2 ) and emission inventory data on the ratio of FF emissions of CO 2 and nitrogen oxides (NO x = NO + NO 2 ). A similar approach was employed by Konovalov et al (2014) to obtain estimates of CO 2 emissions from biomass burning in Siberia by using satellite measurements of carbon monoxide (CO) and of aerosol optical depth.…”
Section: Introductionmentioning
confidence: 99%